2012
DOI: 10.1039/c2dt30077j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological activity of cymantrene and cyrhetrene 4-aminoquinoline conjugates against malaria, leishmaniasis, and trypanosomiasis

Abstract: Organometallic analogues of chloroquine show promise as new antimalarial agents capable of overcoming resistance to the parent drug chloroquine. Here, the synthesis and characterization of three new cymantrene (CpMn(CO)(3)) and cyrhetrene (CpRe(CO)(3)) 4-aminoquinoline conjugates with either an amine or amide linker are reported. The antimalarial activity of the new organometallic conjugates N-(2-(7-chloroquinolin-4-ylamino)ethyl)-4-cymantrenylbutanamide (3), N-(2-(7-chloroquinolin-4-ylamino)ethyl)-4-cyrhetren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 53 publications
3
47
0
Order By: Relevance
“…Again, only negligible differences in anti‐leishmanial/anti‐trypanosomal activity were observed for the rhodium compound relative to the iridium one. Although these are quite promising results,15 the metal–NHC complexes are still about two orders of magnitude less active than the reference drug pentamidin, which has low nanomolar activity under similar conditions and a selectivity index of approximately 3500. Thus, these metal–NHC compounds miss the definition and activity criteria for hit and lead development as defined by the WHO/TDR (World Health Organization, Special Programme for Research and Training in Tropical Diseases) 16…”
Section: Resultsmentioning
confidence: 99%
“…Again, only negligible differences in anti‐leishmanial/anti‐trypanosomal activity were observed for the rhodium compound relative to the iridium one. Although these are quite promising results,15 the metal–NHC complexes are still about two orders of magnitude less active than the reference drug pentamidin, which has low nanomolar activity under similar conditions and a selectivity index of approximately 3500. Thus, these metal–NHC compounds miss the definition and activity criteria for hit and lead development as defined by the WHO/TDR (World Health Organization, Special Programme for Research and Training in Tropical Diseases) 16…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23][24][25][26] This strategy was found very successful with ferroquine (FQ), a ferrocenyl analogue of the antimalarial drug chloroquine (CQ), as FQ is active on CQ-resistant Plasmodium falciparum strains. Furthermore, intensive chemical biology studies have recently allowed unveiling additional modes of action for FQ compared to the parent drug in FQ, which were attributed to the presence of the organometallic unit.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported the facile synthesis of three new triazole-derivatized cymantrene complexes (3)(4)(5) in good yield, all of which have been structurally characterized using a variety of techniques. The incorporation of either a para or meta-amine group into the pendant phenyl ring at the 4-position of the triazole moiety does not adversely affect the "click" reaction used to form it.…”
Section: Discussionmentioning
confidence: 99%
“…3 Excitingly, we found that all three click products 3-5 were more active than cymantrene 1 at reducing the growth rate of cells by 50% to that of the controls when tested against Trypanosoma brucei (Table 4). The advantage of having a cymantrene spectroelectrochemical redox tag attached to the triazole unit has been pointed out by Geiger,6 allowing for the possibility of spectroscopic or electrochemical monitoring of the compound in cell cultures, and photochemical activation (release) of the pendant CO groups.…”
Section: Trypanocidal Activity Studiesmentioning
confidence: 99%
See 1 more Smart Citation